Alcohol use disorder due to social isolation after a nuclear disaster in Fukushima - Morita, Tomohiro (BMJ Case Rep, 2015)
It is well-known that a nuclear disaster causes health problems including cancer, however, information on mental disorders linked to a nuclear disaster is limited. On 11 March 2011, there was a serious nuclear power plant accident in Fukushima, Japan. Subsequently, in October 2012, a 78-year-old man living 31 km from the plant was admitted to the hospital with head trauma. This was his third physical trauma since the nuclear accident. A thorough interview revealed that his alcohol intake had increased after the disaster, suggesting that his injuries might be related to alcohol use. The diagnosis of alcohol use disorder was established based on the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders. He had been exposed to social isolation after evacuation of his neighbourhood. Using education and intervention, he was successfully treated. We should recognise that a nuclear disaster might cause social isolation among the elderly, leading to mental disorders and alcohol use disorder. Early diagnosis and intervention might be beneficial for individuals presenting the above symptoms.